Mn4-xGaxN Thin Films for Ferrimagnetic Spintronics - Coey, John; Rode, Karsten (My University, 2023)
Ferrimagnetic compensation in Mn4−xGaxN (0<x<0.27) thin films grown by sputtering on (001) MgO is determined from magnetisation and Anomalous Hall effect measurements and compared with results on the bulk material. Compensation appears in films with x >0.15 and it occurs at 235 K when x = 0.18. A greater amount of Ga-doping is required to achieve compensation in the bulk, where room-temperature compensation is at x = 0.26. The differences are discussed in terms of Ga site occupancy in the Mn4N structure, and an effect of the change of easy axis of the triangular ferrimagnetic spin structure from [111] in the bulk to [001] in the tetragonally-distorted films.
Keywords: Anomalous Hall effect, Compensated Ferrimagnet, Mn4−xGaxN thin films, Non-collinear spin structure; Nanoscience & Materials; Applied physics; Condensed matter, electronic, magnetic and superconductive properties; Magnetism and spin electronics; Nanotechnology; Nanotechnology